Improved statistics for economic growth : a compendium of views and suggestions from individuals, organizations, and statistics users - United States (Washington : U.S. Govt. Print. Off., 1965)
The book contains the report of United States Congress. Joint Economic Committee. Subcommittee on Economic Statistics on the performance of economic activities of the country.
At head of title: 89th Congress, 1st session. Joint Comittee print.
Includes bibliographic references
usc 29/01/2019
Loans
Keywords: Statistics; Economic development; Economic history; United States